The effectiveness of blended learning organization - Karasiova, Olena (Рівненський державний гуманітарний університет, 2025)
The article mainly focuses on the problem of effective blended learning organization at higher educational institutes and its advantages in educational process. At present, blended learning is the best way to organize students’ learning activity using supportive environment, individualized learning, gamification, different tools, methods, and techniques. Its advantages such as flexibility, cost effectiveness, accessibility and others enable teachers organize educational process most effectively.
Keywords: blended learning; advantages; effectiveness